Representasi verbal siswa sekolah menengah pertama dalam mengkomunikasikan faktor prima - Sukiyanto Sukiyanto; Fitry Wahyuni (Mahesa Research Center, 2021)
The purpose of this study was to describe students' communication in solving prime factors using written and oral communication. This study uses a qualitative and descriptive approach. The subjects of this study were 46 seventh grade students of Simanjaya Lamongan, East Java, Indonesia, Middle School who had obtained prime factor material. Data analysis was obtained by using a test of prime factors and interviews. Based on the results of data analysis, it was concluded that: 1) Written communication, as many as 40 students were able to communicate in writing with a percentage of 87% and 6 students were unable to communicate in writing with a percentage of 13%; 2) Oral communication, at this stage interviews were conducted by taking the subject as many as two students taken from one student who is able to communicate in writing and one student who is not able to communicate in writing, the results obtained that students are able to communicate in writing are also able to communicate verbally. verbally, while students who are not able to communicate in writing, it turns out that students are able to communicate orally. From the explanation above, it can be concluded that students are able to explain concepts into mathematical language, students are able to explain mathematical arithmetic operations, students are able to explain mathematical solutions and students are able to convey ideas or opinions. Thus, students can communicate in writing and orally well in solving prime factors.